Optimalisasi Titik Pembocoran Perpipaan Air Minum Menggunakan Konsep Himpunan Dominasi Graf di Desa Lendola - Maro, Landerius; Leto, Chrisyantus; J. Selly, Julminggu; Ena, Maktisen (Jurnal Media Informatika, 2024)
Very high population growth has a direct impact on drinking water needs in the Lendola Village area. This triggers competition between communities in the effort to obtain drinking water, namely by leaking drinking water pipes that pass through people's homes without caring about each other. This study aims to optimize leakage of drinking water pipes and design of piping networks in the Lendola Village area by applying a domination set to the graph. The piping network that is used according to actual conditions, then applied to the graph form then looks for the domination set to get the minimum domination node. The results of this study are in the form of domination points which are used as leak points and the creation of a drinking water piping network that passes through all of these domination points in the Lendola Village area.